How to Improve the Employee Productivity of Banking System in India – a Theory of Accountability Based Analysis - P. S. Aithal; Prasanna Kumar; Mike Dillon, (International Journal of Management, Technology and Social Sciences (IJMTS), 2018)
The recently developed theory called Theory of Accountability (Theory A) for organizations of 21st century identifies the various factors which affect the organizational human resources performance. The essential components identified to improve the productivity of any organization based on the postulates of Theory A are (1) Planning, (2) Target setting, (3) Motivation, (4) Work Strategies, (5) Responsibility, (6) Role model, (7) Monitoring & Guiding, and (8) Accountability. The objective of this paper is to apply the components of Theory A to Indian Banking system and to study how to improve the productivity of the banking system for economic progress in India. Accordingly we analysed the business model and the organizational strategy of Indian Banks in terms of their business objectives, service planning, target setting for the employees, employee motivational factors, working strategies to improve productivity, selfand mutual responsibilities among individual employees and in their teams, concept of role model in banking service innovation, continuous monitoring and guiding strategies, and finally accountability of each and every employee at different organizational levels. The applicability of Theory A on both private and public sector banks are discussed in general and suitable suggestions are proposed to the banking sector to improve productivity based on the postulates of Theory A.